Respuesta :

If x is the independent variable then y is the dependent variable so it would be y=something
you take x-y-4=0 and make it so that y is alone on one side
x-y-4=0
Add four to both sides 
x-y=4
subtract x
-y=-x+4
divide by -1 and get your answer
y=x-4

Answer:

The  equation written in a function notation, with x the independent variable is [tex]y=x-4[/tex].

Step-by-step explanation:

Consider the provided function represented by the equation x - y - 4 = 0

Now convert the provided equation with x the independent variable.

[tex]x-y-4=0[/tex]

Add both side by y.

[tex]x-y-4+y=0+y[/tex]

[tex]x-4=y[/tex]

The above equation can be written as:

[tex]y=x-4[/tex]

Now the value of y is deeding on the value of x. Where the value of x is independent variable.

Hence, the  equation written in a function notation, with x the independent variable is [tex]y=x-4[/tex].